The Indochinese Refugees in Canada: A Preliminary Survey - Cadchumsang, Jaggapan (Journal of Social Sciences, Chiang Mai University, 2024)
This article is a preliminary survey of Indochinese refugees in Canada. The content presented in this article covers three main issues: the background of the refugees and resettlements of these refugees, their adaptation and integration into Canadian society, and their constructions of translocal communities and ethnicity. The sociopolitical changes and upheavals arising from the victory of communism in Vietnam, Laos, and Cambodia had resulted in an exodus of their citizen, who consequently became refugees in many countries. Canada was among the countries that accepted many refugees from the former Indochina during the mid-1970s to the 1980s. These waves of refugees have resettled in different areas of Canada, particularly main cities in provinces across the country. In the early period of their resettlements, which the government and private sectors actively supported, the Indochinese had to adapt themselves to new environments and ways of life. After integrating into Canadian society, they started to build communities based on the culture brought from their motherland and the culture in the host country. Interestingly, various forms of socio-cultural dynamics recently taking place in Canadian society, including emerging ethnocultural diversity and complexity within the Indochinese communities, have led to clashes, negotiations, and the construction of identities in different dimensions.